A review of rare earth elements in the Western Belt of Peninsular Malaysia - Nur ‘Aishah Zarime; Nurul Afifah Mohd Radzir; Nur Suraya Ahmad; Warishah Abdul Wahab; Nur Syahirah Alias; Badariah Solemon; Rohayu Che Omar; Rasyikin Roslan; Wan Zuhairi Wan Yaacob; Abdul Ghani Rafek (Universiti Kebangsaan Malaysia, 2025)
Rare Earth Elements (REEs) alternatively termed non-energy minerals, have emerged as a greatly coveted resource for industries focused on high-technology and low-carbon applications. The Western Belt of Peninsular Malaysia has the potential to yield ion-adsorption rare earth element (REE) clays, which are found in extensive weathered granitic crusts that frequently exhibit high-grade ion-adsorbed REEs. Currently, global demand is increasing, and there are concerns over future availability. Malaysia is also recognized as a country with significant REEs material production, along with the United States, Australia, Brazil, India, Russia, Thailand, and Vietnam. This paper has two main objectives, which were; i) to conduct a literature review related to REE in the Western Belt and ii) to identify distribution pattern of REE deposits in Western Belt of Peninsular Malaysia. The methodology for this paper is all the data collected from ranges of sources including geological surveys, academic literature, and industry reports. Sites were selected based on their geological characteristics and historical data indicating the presence of REE mineralization. This extensive review also highlights the geochemistry, geological setting, exploration and extraction associated with REEs in the Western Belt of Peninsular Malaysia. The insights presented here can aid the government, researchers, and decision-makers in gaining a better understanding of REEs, enabling them to continue producing rare earth-dependent products and meeting global demand.